Digital leadership transformation in India - Jeedigunta, Sai (Global journal of Business and Integral Security, 2023)
This research study examines digital leadership transformation in India. The purpose of this study is to provide an understanding of the current state of digital leadership in India and to explore the factors driving the transformation of digital leadership. A secondary data analysis approach was used to investigate the current state of digital leadership in India. Data was collected from existing literature, reports, and statistical databases. The findings of the study indicate that digital leadership transformation in India is being driven by the rapid adoption of digital technologies, the increasing availability of digital talent, and the need to develop innovative strategies and solutions for a prosperous future. Furthermore, the study found that digital leadership transformation is also driven by the need to enable a culture of innovation, create a more agile and adaptable organization, and enable more effective decision-making. The research provides insights into the current state of digital leadership transformation in India and highlights potential areas for further research.